Morphology transformation of multicompartment self-assemblies of ABC triblock copolymers. (5th May 2017) - Cong, Yang; Zhou, Qi; Xu, Yuan; Fang, Jiaojiao; Zhu, Kaiyun
Abstract: Morphology transformations of multicompartment assemblies of polystyrene-polyisoprene-poly(2-vinylpyridine), PS-PI-P2VP, was demonstrated. As the solvent quality is continuously varied the triblock copolymer experiences transformations from core-shell-corona micelles to particles with perforated lamellae, or from multicompartment micelles into PI-perforated PS-P2VP lamellae. Such multicompartment self-assemblies and morphology transformations may find potential applications as vehicles for multi-drugs or other active substances. Graphical abstract: Highlights: PS-PI-P2VP self-assembles into patchy multicompartment micelles in neutral solvents. The micelles are transformed into hierarchical structures upon addition of selective solvents. The morphology transformation is sensitive to solvent quality.